Genetic insights into immune mechanisms of Alzheimer’s and Parkinson’s disease - Nott, Alexi; Holtman, Inge R. (Frontiers in Immunology, 2023)
Microglia, the macrophages of the brain, are vital for brain homeostasis and are implicated in a broad range of brain disorders. However, the exact role of microglia in specific neurodegenerative and neuroinflammatory disorders is a topic of debate. Genetic studies offer valuable insights into understanding causality rather than just observing a correlation. Genome-wide association studies (GWAS) have identified many genetic loci that are linked to susceptibility to neurodegenerative disorders. (Post)-GWAS studies have determined that microglia play an important role in the development of Alzheimer’s disease and Parkinson’s disease. The process of understanding how individual GWAS risk loci affect microglia is ongoing and requires large genomic datasets and computational tools to analyse the data. In this review, we discuss the key concepts and challenges in the post-GWAS interpretation of Alzheimer’s disease and Parkinson’s disease GWAS risk alleles. Post-GWAS challenges include the identification of target cell (sub)type(s), causal variants, and target genes. Crucially, the prediction of GWAS-identified disease-risk cell types, variants and genes require validation and functional testing to understand the biological consequences within the pathology of the disorders.